2014
DOI: 10.1108/jpbm-03-2014-0516
|View full text |Cite
|
Sign up to set email alerts
|

“Natural” labeling and consumers’ sentimental pastoral notion

Abstract: Purpose – This study aims to investigate the appeal of “natural” labeling and builds on past research which suggests that people may have a naïve pastoral view of nature and natural entities. “Natural” labeling is pervasive in supermarkets across the USA. Design/methodology/approach – This paper employs a multi-method approach to examine consumer perceptions and beliefs about products labeled “natural”. Qualitative responses are solicite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
55
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 48 publications
2
55
0
Order By: Relevance
“…In fact, it has been found that organic food choice appears to be driven by modern health concerns (Devcich, Pedersen, & Petrie, 2007), negative associations with chemicals (Dickson-Spillmann, Siegrist, & Keller, 2011) as well as scepticism about functional food developments (Aschemann-Witzel, Maroscheck, & Hamm, 2013) and unknown ingredients (Evans, Challemaison, & Cox, 2010). Naturalness in food is sought because of associations of more traditional and 'authentic' processing, leading to assumptions about favourable health effects (Amos, Pentina, Hawkins, & Davis, 2014). Consequently, food producers respond by altering their ingredient lists in order to move closer to the idea of 'clean label' foods.…”
Section: Clean Label Consumer Trendmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, it has been found that organic food choice appears to be driven by modern health concerns (Devcich, Pedersen, & Petrie, 2007), negative associations with chemicals (Dickson-Spillmann, Siegrist, & Keller, 2011) as well as scepticism about functional food developments (Aschemann-Witzel, Maroscheck, & Hamm, 2013) and unknown ingredients (Evans, Challemaison, & Cox, 2010). Naturalness in food is sought because of associations of more traditional and 'authentic' processing, leading to assumptions about favourable health effects (Amos, Pentina, Hawkins, & Davis, 2014). Consequently, food producers respond by altering their ingredient lists in order to move closer to the idea of 'clean label' foods.…”
Section: Clean Label Consumer Trendmentioning
confidence: 99%
“…Research has looked into what consumers associate with certain ingredients using different techniques, as, for example, word association tasks and free listing (Varela, Ares, & Fiszman, 2013; or qualitative methods of association (Amos et al, 2014). So far the potential of the projective mapping method for studying ingredient perception is under-explored.…”
Section: Projective Mappingmentioning
confidence: 99%
“…Label represents a third sub-factor. Amos, Pentina, Hawkins, & Davis (2014) suggested that food products labeled with natural claims are perceived to be less harmful and healthier, with superior instrumental attributes, and possessing higher nutritional value and lower human contamination. Liu, Hooker, Parasidis, & Simons (2017) found that the presence of an all-natural FOP label improves consumers' perceptions of product quality and nutritional content.…”
mentioning
confidence: 99%
“…Although in legislation there is no difference between ‘natural’ and ‘artificial’ E-numbers [ 32 ], consumers think that ‘natural is safe’. Consumers use ‘natural’ as a simple feature that labelled on food products show that these products contain superior attributes and are perceived to be less harmful and healthier than conventional [ 33 ]. Although the price for natural ingredients was generally higher, companies reported that these products were selling well because of the positive narrative attached to them.…”
Section: Resultsmentioning
confidence: 99%